The Minimum Effective Training Dose Required for 1RM Strength in Powerlifters - Androulakis-Korakakis, Patroklos; Michalopoulos, Nick; Fisher, James P.; Keogh, Justin; Loenneke, Jeremy P.; Helms, Eric; Wolf, Milo; Nuckols, Greg; Steele, James (Frontiers in Sports and Active Living, 2021)
The aim of this multi-experiment paper was to explore the concept of the minimum effective training dose (METD) required to increase 1-repetition-maximum (1RM) strength in powerlifting (PL) athletes. The METD refers to the least amount of training required to elicit meaningful increases in 1RM strength. A series of 5 studies utilising mixed methods, were conducted using PL athletes & coaches of all levels in an attempt to better understand the METD for 1RM strength. The studies of this multi-experiment paper are: an interview study with elite PL athletes & highly experienced PL coaches (n=28), an interview & survey study with PL coaches and PL athletes of all levels (n=137), 2 training intervention studies with intermediate-advanced PL athletes (n=25) & a survey study with competitive PL athletes of different levels (n=57). PL athletes looking to train with a METD approach can do so by performing approximately 3-6 working sets of 1-5 repetitions each week, with these sets spread across 1-3 sessions per week per powerlift, using loads above 80% 1RM at a Rate of Perceived Exertion (RPE) of 7.5 to 9.5 for 6-12 weeks and expect to gain strength. PL athletes who wish to further minimize their time spent training can perform autoregulated single repetition sets at an RPE of 9-9.5 though they should expect that strength gains will be less likely to be meaningful. However, the addition of 2-3 back-off sets at approximately 80% of the single repetitions load, may produce greater gains over six weeks while following a 2-3-1 squat-bench press-deadlift weekly training frequency. When utilizing accessory exercises in the context of METD, PL athletes typically utilize 1-3 accessory exercises per powerlift, at an RPE in the range of 7-9 and utilize a repetition range of approximately 6-10 repetitions.